The Effect of Rapid Learning Strategy on Creative Thinking and Performance of Reception and Blocking Skills in Volleyball - Alia Hussein Farhan; Fadia Abdul Hussein Kadhim; Salah Mahmoud Salman; Tahseen Hosni Tahseen (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
This study Purpose to develop and implement educational exercises Based on a rapid learning strategy to increase volleyball reception and between blocking skills middle school students, During the exam its impact but creative thinking. The researcher hypothesized that both experimental and control groups would be shown. Significant improvements from pre- test to post- test, and that the experimental group will perform significantly better. The control group in the test steps after both creative thinking and volleyball skill performance. A quasi- experimental design was used with 60 fifth- grade female students is randomly selected from Al- Mutamayyat Girls’ Secondary School (under the Second Karkh Education Directorate, Baghdad) below 2023– 2024 educational year. Validated instruments were administered for testing. Creative thinking and receiving/ blocking performance. The experimental group complete eight instructional units (one 45- minute session per week over eight weeks), with 30 minutes of each session Dedicated to the rapid learning exercises. Continue with the control group the standard physical education curriculum, While the intervention happened between April 3 and April 26, 2024. All data was treated using SPSS. The analysis This embedding was revealed rapid learning Exercises in volleyball lessons created measurable gains I both technical execution and creative thinking between fifth- grade students. Based on these findings, Teacher design similar activities It should include conscious actions that require cognitive flexibility and real- time problem Solution Doing this keeps students mentally engaged while improving their physical skills.